Bahasa Inggris - Luthfiana Nurtamara; Dewi Amelia Widyastuti (Universitas Negeri Jakarta, 2023)
In the scientific education, improving the argumentation skills in socioscientific issues was very important to educate young people as an active society. The aim of this research was to evaluate the implementation impact of problem based learning to the students skils of evidence based argumentation of socioscientific issues.Total of 21 students of Grade XII MIPA of senior high school at surakarta city were used as the sample in the learning process with biotechnology topic. The times taken for the learning activity were 4 week with 4 times of class meeting every week. Pre-test and post-test were applied to 21 students in order to measure of students skills in constructing the argument of socioscientific issues. . The differences between pre-test and post-test scores for each aspects of evidence-based argument, in sequence, are as follows: 61,11 and 92,06 for claims; 30,16 and 84,13 for evidence; and 28,97 and 78,17 for connection claim to evidence. Statistically test for Wilcoxon rank test score for evidence based argument resulted p-value (0,00) which was < 0,05. This means that score of evidence based argument was improved significantly. In the case of qualitative data used, observation during learning process, learning transcipt, result of students works within learning activity as well as interview activity showed that PBL learning had improved the skill of evidence-based argument of science students.